Diversidade de elementos transponíveis em três espécies de lagartos no sul do brasil, com ênfase em homonota uruguayensis: (phyllodactylidae: squamata) - (:unkn) unknown (Universidade Federal do Pampa, 2022)
Transposable elements (TEs) are repetitive DNA sequences that have the characteristic of changing their position in chromosomes, which can influence the entire genome structure. They are classified into two Classes based on their transposition system: retrotransposons, transpose via an RNA intermediary; and the transposons, transpose via the DNA intermediate. The reptilian mobiloma presents a rich diversity of TEs, in particular, the Squamata reptiles have presented a different panorama in the composition, diversity and activity of TEs in relation to other vertebrates, which makes the study of these repetitive sequences in the genome of these species, quite interesting and promising. The gecko Homonota uruguayensis, better known as Gekko-do-campo, belongs to the Phyllodactylidae family, has a distribution restricted to part of the Pampean region of Rio Grande do Sul - RS and Uruguay, and has aroused the interest of researchers from ecological, taxonomic and ecological perspectives. of population genetics. However, on the genetic diversity of this species, from the point of view of the TEs, no study has been carried out so far. The other species analyzed, Salvator merianae which has a wider distribution in RS and Hemidactylus mabouia an exotic species, were analyzed in a preliminary way and used as comparative models. Thus, the present work aims to investigate the transposable elements in Squamata reptiles, as a way of contributing to the genetic diversity of species found in the Pampa Biome. Samples of the geckos' caudal tissue were collected, without the need to sacrifice the animals. Genomic DNA extractions were performed from caudal tissue samples with a commercial purification kit, following the manufacturer's recommendations or by the phenol - chloroform purification method. The identification of transposable elements of interest was performed by amplification via PCR (Polymerase Chain Reaction), using specific primers for each element (14 sets of primers). The amplified DNA fragments were subjected to electrophoresis in 1% agarose gel, visualized and recorded in a photodocumentator under ultraviolet light. As a result, 12 different TEs were detected in H. uruguayensis, of both classes and less than 10 TEs amplified in S. merianae and H. mabouia. Although preliminary, these are the first TEs identified in the genome of H. uruguayensis, including the presence of an element possibly involved in horizontal transfer. In view of the results obtained, it is clear the importance of studies of transposable elements in the various eukaryotic groups, to understand the diversity they have in the genomes, especially in poorly studied species, since such species can hide a rich source of little explored information.
Keywords: Biologia Molecular; Elemento Transponível; Squamata; Molecular Biology; Transposable Element; Squamata; CNPQ::CIENCIAS BIOLOGICAS